1980
DOI: 10.1002/j.2050-0416.1980.tb06884.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Raised Temperatures During Steeping and Germination on Proteolysis During Malting

Abstract: Raising the temperature from 16°C to 20°C or 25°C for prolonged periods during steeping or germination reduces HWE and TSN and slows down wort separation in laboratory mashes. When the higher temperatures are applied only during the last steep or the first two days of germination the initial rate of modification is accelerated, as is the development of a-amylase and endopeptidase. After four or five days germination the levels of enzyme activity are substantially lower than in the control malt. However, some b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 8 publications
4
17
0
1
Order By: Relevance
“…It is equally remarkable that the proteinase enzyme activity increases in all the malt varieties were moderate or not as pronounced as in the carboxypeptidase enzyme. Although several-fold increases in proteinase activity were reported during sorghum germination 3,21,26,37 and barley germination 6,7,10,30,31,33 , our results are in consonance with the moderate increase reported earlier by Evans and Taylor 19,20 .…”
Section: )Jjigx Sj I\xvegxerxw Sr Tvsximrewi Egxmzmx]supporting
confidence: 92%
“…It is equally remarkable that the proteinase enzyme activity increases in all the malt varieties were moderate or not as pronounced as in the carboxypeptidase enzyme. Although several-fold increases in proteinase activity were reported during sorghum germination 3,21,26,37 and barley germination 6,7,10,30,31,33 , our results are in consonance with the moderate increase reported earlier by Evans and Taylor 19,20 .…”
Section: )Jjigx Sj I\xvegxerxw Sr Tvsximrewi Egxmzmx]supporting
confidence: 92%
“…Steeping at temperatures up to 25°C compared with 15°C, germinating at 20-24°C instead of 16°C and withering at 30-37.5°C compared with 60°C were shown to result in a faster cytolytic modification. Also other authors found an enhanced cell wall degradation when steeping (22,26) and germinating at higher temperatures (10,21,32) and at lower withering temperatures (41,42,68). The found optimal parameters combined in the accelerated malting programmes succeeded sufficiently in the shorter process.…”
Section: Resultsmentioning
confidence: 79%
“…Proteolytic modification is said to be reduced at higher germination temperatures resulting in lower free amino nitrogen (FAN) and soluble nitrogen content and thus decreased Kolbach indices, which can be insufficient for adequate yeast nutrition and foam stability in the final beer (12,16,21,28,29). In addition, Baxter and coworkers (13,26) and Reeves et al (25) observed an impaired filterability of mashes produced from warm steeped and germinated malt. On the other hand, a generally improved cytolytic modification could be observed when applying increased steeping and germination temperatures, as shown by several authors (10,12,21,22,(26)(27)(28)(29)31,34).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Após o efeito indutor inicial, observar-se-ia uma queda na atividade das ß-glucanases, amilases e proteases, antes da finalização do processo, resultando em baixa produção de extrato e nitrogênio solúvel, enquanto a viscosidade permaneceria alta (BAXTER & O FARRELL, 1980;BRIGGS, 1998). Como explicado anteriormente, até completar três dias de germinação, foi adicionada água aos grãos de cevada em quantidade suficiente para que atingissem umidade em torno de 46% e o efeito da temperatura utilizada durante a germinação também foi observado durante esse procedimento.…”
Section: B Bunclassified